Experimental study of energy distribution in ion-beam lithography - Myrzabekova, M. M.; Guseinov, N.R.; Muratov, M.M.; Gabdullin, M.T.; Nemkayeva, R. R.; Tolkynbayeva, T.; Shabelnikova, Ya. L.; Zaitsev, S. I. (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
The paper reports two important results. Conducted a rigorous comparison of the sensitivity of the resist is polymethylmethacrylate (PMMA) to the irradiation of electron and ion beams. It is shown that, as in the case of electron irradiation, the resist shows both positive (at low doses) and negative (at higher doses) behavior of sensitivity. But compared with the electronic exposure, sensitivity of the resist is approximately a thousand times higher to the ion exposure, both the positive and negative areas.....
Keywords: electron; ion beams